2020
DOI: 10.3389/fimmu.2020.01024
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Microglia and Astrocytes in the Neurovascular Unit

Abstract: The interaction between microglia and astrocytes significantly influences neuroinflammation. Microglia/astrocytes, part of the neurovascular unit (NVU), are activated by various brain insults. The local extracellular and intracellular signals determine their characteristics and switch of phenotypes. Microglia and astrocytes are activated into two polarization states: the pro-inflammatory phenotype (M1 and A1) and the anti-inflammatory phenotype (M2 and A2). During neuroinflammation, induced by stroke or lipopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
239
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(289 citation statements)
references
References 150 publications
(186 reference statements)
4
239
0
3
Order By: Relevance
“…Microglia play a key role following stroke, and the M1 phenotype typically releases pro-inflammatory mediators, while the M2 phenotype suppresses the harmful processes associated with ischemia. Numerous studies have shown that the interaction of various cells (i.e., astrocytes, oligodendrocytes, neurons), specific cytokines, drugs, and other extracellular components can promote microglia phenotype conversion (Kim and Cho, 2016 ; Pepe et al, 2017 ; Zhang et al, 2019a ; Liu L. R. et al, 2020 ). Furthermore, a large number of studies have focused on the combined intervention of miRNAs and microglia; however, the role of miRNAs in the phenotypic transformation of microglia might not be limited to reducing the release of pro-inflammatory factors (Kim and Cho, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia play a key role following stroke, and the M1 phenotype typically releases pro-inflammatory mediators, while the M2 phenotype suppresses the harmful processes associated with ischemia. Numerous studies have shown that the interaction of various cells (i.e., astrocytes, oligodendrocytes, neurons), specific cytokines, drugs, and other extracellular components can promote microglia phenotype conversion (Kim and Cho, 2016 ; Pepe et al, 2017 ; Zhang et al, 2019a ; Liu L. R. et al, 2020 ). Furthermore, a large number of studies have focused on the combined intervention of miRNAs and microglia; however, the role of miRNAs in the phenotypic transformation of microglia might not be limited to reducing the release of pro-inflammatory factors (Kim and Cho, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this immunocompetent response, aggregation of pattern recognition receptors (PRRs), which are mainly toll-like receptors (TLRs), activate microglia and consequently trigger neuroinflammation [ 18 ]. Stimulated M1 phase microglia have been indicated to activate astrocytes directly [ 19 ]. Glia-mediated neuroinflammation has been linked to the pathogenesis of various NDs, including AD, PD, and MS [ 20 , 21 ].…”
Section: Inflammation and Mitochondrial Dysfunction Implicated Inmentioning
confidence: 99%
“…The immune response in ischemic stroke is regulated by various glial cell types that also interact among themselves to regulate inflammation, and these glia-mediated mechanisms can exert both beneficial and detrimental effects (13). Astrocytes and microglia are two important components of the neurovascular unit, and both are activated in response to ischemic stroke, as well as other types of CNS injuries (38). It has been previously shown that activated microglia can induce reactive astrogliosis with neurotoxic effects (39), but the mechanisms that regulate microglia activation are still not completely clear.…”
Section: Chrdl1 Does Not Impact Reactive Gliosismentioning
confidence: 99%